On the k-generalized padovan numbers - Lee, Gwangyeon (Utilitas Mathematica, 2018)
The fc-generalized Padovan sequence (Equation presented) is defined as follows: (Equation presented) and for n > k ≥ 2, (Equation presented) If k = 1, then 1-generalized Padovan sequence is the Fibonacci sequence. If k = 2, then 2-generalized Padovan sequence is the Padovan sequence. In this paper, we consider relationship between the nth k-Padovan number and the permanent and the determinant of (0, l)-matrices. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.